The Effectiveness of Sensory Processing Training on Couples’ Adjustment - Aminaei Chaturudi, Fereshteh; Askari , Mahin; Baniasadi , Hassan (Iranian Journal of Neurodevelopmental Disorders, 2024)
This study aimed to examine the effectiveness of sensory processing training on marital adjustment in couples experiencing marital discord. The study utilized a quasi-experimental pretest-posttest design with a control group. The statistical population included couples seeking help at family counseling centers in Kerman in 2023, from which 30 participants were purposively selected and randomly assigned to experimental (n = 15) and control (n = 15) groups. Data were collected using the Graham Spanier Marital Adjustment Questionnaire (1976), a 32-item instrument assessing the quality of marital relationships. The experimental group participated in a 10-session sensory processing training program designed to address sensory sensitivities and improve emotional regulation and communication, while the control group received no intervention. Data were analyzed using analysis of covariance (ANCOVA) with SPSS version 27. The results of ANCOVA revealed a significant effect of sensory processing training on marital adjustment (F = 240.349, p < 0.001, η² = 0.811). The intervention explained 81.1% of the variance in marital adjustment scores, demonstrating substantial improvement in the experimental group compared to the control group. Sensory processing training was found to be an effective intervention for enhancing marital adjustment by addressing sensory sensitivities and improving emotional regulation and interpersonal communication. These findings suggest that sensory-based interventions can complement existing therapeutic approaches to address marital discord. Further research is recommended to explore the long-term effects and applicability of sensory processing training across diverse populations and cultural contexts.